Whole genome expression analyses of single- and double-knock-out mice implicate partially overlapping functions of alpha- and gamma-synuclein - Kuhn, Melanie (2007)
Alpha-synuclein has been implicated in the pathogenesis of Parkinson’s disease. The function of α-synuclein has not been deciphered yet, however, it might play a role in vesicle function, transport or as a chaperone. Alpha-synuclein belongs to a family of three proteins, which includes β- and γ-synuclein. Gamma-synuclein shares 60% similarity with α-synuclein. Similar to α-synuclein, a physiological function for γ-synuclein has not been defined yet but it has been implicated in tumorgenesis and neurodegeneration. Interestingly, neither alpha- (SNCA(−/−)), gamma- (SNCG(−/−)) nor alpha/gamma (SNCA_G(−/−)) deficient mice present with any obvious phenotype. Using microarray analysis we thus investigated whether deficiency of alpha- and gamma-synuclein leads to similar compensatory mechanisms at the RNA level and whether similar transcriptional signatures are altered in the brain. Sixty-five genes were differentially expressed in all mice. SNCA(−/−) mice and SNCG(−/−) mice shared 84 differentially expressed genes, SNCA(−/−) and SNCA_G(−/−) 79 genes, and SNCG(−/−) and SNCA_G(−/−) 148 genes. For many of the physiological pathways such as dopamine receptor signaling (down-regulated), cellular development, nervous system function, and cell death (up-regulated), we found groups of genes that were similarly altered in SNCA(−/−) and SNCG(−/−) mice. In one of the pathways altered in both models we found Mapk1 as the core transcript. Other gene groups, however, such as TGF-β signaling and apoptosis pathways genes were significantly up-regulated in the SNCA(−/−) mice, but down-regulated in SNCG(−/−) mice. Beta-synuclein expression was not significantly altered in any of the models.